(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The digital revolution in the last decade has drastically changed the transaction Behavior of economic agents, the transaction pattern has shifted to shopping transactions on digital platforms and this demands mobile payment methods, seeing that the Indonesian government is targeting financial inclusion to be> 90% by 2024, In response to this, the Government of Indonesia is trying to increase digital transactions by issuing the QRIS Payment system in August 2019, until January 2021 there have been 42 payment system service providers that are members of the QRIS payment system but Indonesian people still prefer to use cash in shopping, payment using mobile payment is only 8% of all transactions, seeing this, an analysis of the factors that influence the Behavior of using the QRIS payment system will be carried out.The research will be conducted by quantitative Study, model used in this research is a modified UTAUT. The UTAUT basic model has been proven and has been widely used in various countries and cultures to conduct research on acceptance and Behavior of system use and is modified by adding Perceived Security, Trust and Privacy Risk factors Based on the results of the study, it shows that Behavior Intention, Perceived Security, Trust and Privacy Risk are important determinants and have an impact either directly or indirectly on the use of electronic payments besides the ease of use (Effort Expectancy) applications also have a considerable influence on the use of electronic payments. This finding is in line with field conditions in the QRIS payment system.